An Investigation into EFL Students Perceptions Regarding the Use of Google Translate in Translation courses -a case study at UD-UFLS - Nguyễn Hải Thủy Dương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis aimed to investigate the EFL students’ perceptions on the use of Google Translate as a tool in bilingual translation classes for English-major students at UFL. This also served as the foundation for suggestions for effective GT use in translation learning programs for EFL students at UFL.